2007
DOI: 10.1103/physrevb.75.014522
|View full text |Cite
|
Sign up to set email alerts
|

Superconductor-to-normal transitions in dissipative chains of mesoscopic grains and nanowires

Abstract: The interplay of quantum fluctuations and dissipation in chains of mesoscopic superconducting grains is analyzed and the results are applied to nanowires. It is shown that in one dimensional arrays of resistively shunted Josephson junctions, the superconducting-normal charge relaxation within the grains plays an important role. At zero temperature, two superconducting phases can exist, depending primarily on the strength of the dissipation. In the fully superconducting phase ͑FSC͒, each grain acts superconduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 114 publications
(272 reference statements)
3
72
0
Order By: Relevance
“…Schmid [7] and Chakravarty [8] showed that a JJ undergoes a SIT as a function of the junction's shunt resistance, R s , with a critical resistance of R Q , and that the resistance across the junction obeys the power law R T / T 2 R Q =R s ÿ1 . The theory was later extended to JJ arrays and SC wires [9][10][11]. Within these theories, a similar power-law temperature dependence of the resistance at low temperature prevails.…”
mentioning
confidence: 96%
“…Schmid [7] and Chakravarty [8] showed that a JJ undergoes a SIT as a function of the junction's shunt resistance, R s , with a critical resistance of R Q , and that the resistance across the junction obeys the power law R T / T 2 R Q =R s ÿ1 . The theory was later extended to JJ arrays and SC wires [9][10][11]. Within these theories, a similar power-law temperature dependence of the resistance at low temperature prevails.…”
mentioning
confidence: 96%
“…I, these topological excitations produce finite resistivity at T Ӷ T c and are believed to be the origin of destruction of superconductivity in narrow wires 30,33 and in dissipative Josepshon junctions arrays. 10,11 It can be shown 2 that defining a field ͑x͒, such that ٌ͑x͒ϵ⌸͑x͒, the generation of topological defects in the field ͑x͒ can be described by a term…”
Section: Modelmentioning
confidence: 99%
“…1,2 On the other hand, dissipation counteracts fluctuations effects, decreasing the lower critical dimension. [3][4][5][6] Some physical realizations of dissipative low-dimensional systems are the well-known resistively shunted Josephson junctions arrays, where the effect of local ohmic dissipation has been intensively studied, [7][8][9][10][11] superconducting grains embedded in metallic films, [12][13][14][15] and Luttinger liquids coupled to dissipative baths. [16][17][18] Narrow superconducting wires with diameter d Ӷ 0 ͑where 0 is the bulk superconducting coherence length͒ are low-dimensional systems in which strong fluctuations of the order parameter affect low-temperature properties.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in fabricating ultra-narrow superconducting nanowires has greatly boosted the interest in studying phase slippage in quasi-one-dimensional superconductors 2 . There has been an intense activity to establish the existence of quantum phase slips (QPS) related to macroscopic quantum tunneling (MQT) [3][4][5][6][7][8][9][10][11] and to study quantum phase transitions between possibly superconducting, metallic and insulating phases in nanowires 4,[12][13][14][15][16][17] . A dissipation-controlled quantum phase transition [18][19][20][21][22][23][24][25] has been predicted in junctions of superconducting nanowires.…”
Section: Introductionmentioning
confidence: 99%